Megapool S.A.: reconstructing a construction company - Arbaiza, Lydia (2004)
Megapool Ltd. is a family business located in Lima, Peru, specializing in the construction of Jacuzzis and saunas. It was created in 1987 to develop general activities in the field of construction and construction supervision, import, distribute and sell materials and accessories and perform other economic activities permitted by Peruvian law. In August 1999, its CEO sought a consultant to reorganize the company and solve its financial problems, as well as to face the growth stage of the business. The consultant must be able to develop a proposal for the reorganization of the company, which implies the analysis of the main areas of the company, as well as the situation of human resources.